A critical air quality science perspective on citizen science in action. Issue 1 (2nd January 2023) - Booker, Douglas; Walker, Gordon; Young, Paul J.; Porroche-Escudero, Ana
ABSTRACT: Air pollution is a hybrid phenomenon, understood and produced through social practices and material environmental processes. This hybridity leads us to engage critically with how air quality science is carried out. In dialogue with the critical physical geography subdiscipline, we propose a critical air quality science (CAQS) framework to study air pollution's sociomateriality. We use CAQS to illuminate four tensions in the dynamics of knowledge production during a citizen science air quality monitoring project: making undone science matter, blurring "insiderness"/"outsiderness", traffic as both life and death, and changing behaviours versus changing systems. Drawing on interviews with citizen scientists, we outline the implications of these tensions for air quality research design and reporting. The CAQS framework provokes critical thought about the consequences of how air quality science understands, creates and communicates knowledge, and how we can reconfigure our relations with the air to minimise air inequalities.